2016
DOI: 10.3727/105221616x691631
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor β Agonist Induces β-Catenin-Dependent Hepatocyte Proliferation in Mice: Implications in Hepatic Regeneration

Abstract: Triiodothyronine (T3) induces hepatocyte proliferation in rodents. Recent work has shown molecular mechanism for T3’s mitogenic effect to be through activation of β-catenin signaling. Since systemic side effects of T3 may preclude its clinical use, and hepatocytes mostly express T3 hormone receptor β (TRβ), we investigated if selective TRβ agonists like GC-1 may also have β-catenin-dependent hepatocyte mitogenic effects. Here we studied the effect of GC-1 and T3 in conditional knockouts of various Wnt pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…Our present data demonstrating a strong hepatomitogenic effect of IS25 and TG68 suggest that these compounds could be useful in regenerative medicine to manage conditions whereby a rapid liver regeneration is required, such as in the living‐related transplantation, or in the elderly status that is characterized by an impaired liver regenerative capacity 38,39 . Indeed, previous studies have shown that T3 and GC‐1 improved the regenerative response of rodent livers after 70% or 90% hepatectomy and stimulated liver cell proliferation in aged rats when given prior to—or after 70% PH 29,40‐42 …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our present data demonstrating a strong hepatomitogenic effect of IS25 and TG68 suggest that these compounds could be useful in regenerative medicine to manage conditions whereby a rapid liver regeneration is required, such as in the living‐related transplantation, or in the elderly status that is characterized by an impaired liver regenerative capacity 38,39 . Indeed, previous studies have shown that T3 and GC‐1 improved the regenerative response of rodent livers after 70% or 90% hepatectomy and stimulated liver cell proliferation in aged rats when given prior to—or after 70% PH 29,40‐42 …”
Section: Discussionmentioning
confidence: 56%
“…Our previous findings showed that T3 and two other analogues—Sobetirome and Eprotirome—exert a powerful mitogenic effect in the liver, suggesting their possible use in regenerative medicine 29,30 . Therefore, we investigated whether TG68 and IS25 could elicit a proliferative response in this organ as well.…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, agents such as triiodothyronine or thyroid receptor-β agonists like GC-1 may have clinical applications in settings of hepatic insufficiency. 8486 …”
Section: Discussionmentioning
confidence: 99%
“…It is known that the process of liver regeneration after PHE is controlled by a whole cascade of growth factors, cytokines, transcription factors; however, the most important of them are hepatocyte growth factor (HGF), epidermal growth factor, transforming growth factor alpha, and angiogenic factors (Alvarado et al 2016, Beier et al 2016, Ibis et al 2017, Kirschbaum et al 2017, Lisman and Porte 2016. Hepatocyte growth factor plays a key role because it induces the transition of hepatocytes to the mitotic phase.…”
mentioning
confidence: 99%